PENERAPAN HUKUM BERBASIS HUKUM PROGRESIF PADA PERTAMBANGAN BATU BARA DI KALIMANTAN SELATAN - Akhmad Sukris Sarmadi (Masalah-Masalah Hukum, 2012)
UU No. 4 year 2009 about Mineral and Coal Mine still felt by nonalignment at small people. where its negative impact exactly felt by environment and society. Inseparable coal mine with industrialization, while industrialization always need the  source of nature which many. In development of natural resources such as those which happened in Indonesia, needed development of real correct natural resources without having to forced so that disregard negative impact of society and environment. For that, comprehending UU No.4 Year 2009 have to comprehend with substansive  and progressive is objective for the prosperity of society without destroying environment. Study in law to mining of coal smolder in south kalimantan can open knowledge forwards law to be developed for the purpose of more progressive